KEMITRAAN CORPORATE SOCIAL RESPONSIBILITY PT PHAPROS DENGAN TAMAN PELANGI MARDI UTOMO - Ervita Rizqi Yuliyana Sari; Retno Sunu Astuti; R. Slamet Santoso (Journal of Public Policy and Management Review, 2023)
PT Phapros is one of the companies implementing CSR in the form of the Partnership and Community Development Program (PKBL). This research examines the Community Development Program of PT Phapros with Taman Pelangi at the Mardi Utomo Home for Beggars, Homeless and Displaced Persons (PGOT) complex. The purpose of this research is to find out the stakeholders involved, the partnership model that is established and the driving and inhibiting factors of the partnership. Descriptive qualitative method used in this study. As a result, there are three stakeholders involved in the partnership between PT Phapros and Taman Pelangi, namely PT Phapros as the company and the Central Java Social Service and the PGOT Mardi Utomo Institution as the government, so it is included in the type of two-party partnership. The partnership model that is established is a mutualistic partnership model in which both parties both know the importance of cooperating and the benefits of this collaboration in achieving goals. Communication, regulation, other institutions and transparency are the driving factors of the partnership. Meanwhile, resources are the inhibiting factor for partnerships. The recommendation from the results of this study is the need for collaboration with institutions outside the partnership to develop empowerment in Taman Pelangi Mardi Utomo.